Managers and the legal environment - Bagley, Constance E. (Thomson/West, 2006)
Recognized and respected for both its inclusion of cutting edge material and for its strong strategic managerial approach, this is one of the most comprehensive and challenging, yet approachable and understandable legal environments texts on the market. It is equally suitable for students with substantial work experience as well as for those who are studying business for the first time. The text fully looks at the subject matter from the perspective of current and future business managers and leaders by providing an in-depth understanding of how law impacts daily management decisions and business strategies. Its integrated treatment of law and management presents a very strategic perspective, showing how the law provides ways for managers to minimize risk and create value, how to use the law to craft solutions to attain core business objectives, and how to spot legal issues before they become legal problems and effectively handle the inevitable legal disputes that arise in the course of doing business